PENTATONIX’S PHONETICAL INTERFERENCE IN PERFORMING “PAPAOUTAI” - Glenn Arnold Yobel; Myrna Laksman-Huntley (Universitas Hasanuddin, 2022)
One of the changes that occurs because of globalization is the change from monolingualism to bilingualism that causes problems that require them to adapt. Pentatonix, an american international artist, was interested to rearrange “Papaoutai” by Stromae and add it to their next album. Their French pronunciation was not perfect according to phonetic transcription in Le Petit Robert 2019. It was interfered by American English pronunciation as Weinreich stated that interference could be found when a multilingual speaker puts one language norm into another language (Weinreich, 2010), The aim of this research is to explain the types and causes of the interference in the song recorded in PTX Vol. III in 2014. The result shows that the interference was caused by under-differentiation of phones, re-interpretation of distinctions, phone-subtitution, liaison-caused mistakes, and inconsistency of Pentatonix when pronouncing the lyrics. There is also meaning-changing mistakes. Keywords: interference, French song reinterpretation, Pentatonix, Papaoutai